LncRNA ZFAS1 promotes growth and metastasis by regulating BMI1 and ZEB2 in osteosarcoma - Liu, Guangfei (Am J Cancer Res, 2017)
Osteosarcoma (OS) is the most common malignant bone tumor in children and adolescents. LncRNAs have recently gained widespread attention and have been shown to have crucial roles in various biological regulatory processes. ZFAS1, a newly identified lncRNA, was shown to be dysregulated in several cancers. However, little is known about the alteration and functional significance of ZFAS1 in OS. In the present study, for the first time, we revealed a functional role of ZFAS1 on OS growth and metastasis. The expression of ZFAS1 was significantly overexpressed in OS samples and cell lines, and upregulation of ZFAS1 is significantly associated with unfavorable prognosis of OS patients. Functional assays also demonstrated that ZFAS1 enhanced the growth and metastatic ability of OS cells in vitro and in vivo. Mechanistically, we found that ZFAS1 positively regulated malignant phenotypes by competitively binding the miR-200b and miR-200c and upregulating BMI1. ZFAS1 also interacted with ZEB2 and regulated ZEB2 protein stability. Furthermore, we demonstrated that SP1 functions as an upstream activated factor of ZFAS1. ZFAS1 may be a potential therapeutic target for OS tumorigenesis and progression.